Pengembangan E-Modul Berbasis Experiential Learning Ditinjau dari Gaya Belajar untuk Meningkatkan Kemampuan Berpikir Kreatif Matematis - Adiastuty, Nuranita; Prayitno, Anggar Titis; Nurmalasari, Nurmalasari (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to develop an experiential learning-based e-module on algebraic forms to enhance the mathematical creative thinking abilities of junior high school students. The method used is Research and Development (R&D) with the ADDIE model consisting of five stages: analysis, design, development, implementation, and evaluation. The e-module is developed using Canva and Corel Draw, then converted into an interactive flipbook through the Heyzine platform. A validation sheet is used to assess the validity level of the developed e-module. The resulting data is analyzed descriptively quantitatively. The validation results by material and media experts show a validity level of 85% (very valid). The practicality of the e-module was assessed by teachers at 88.89% and by students at 81.15% (very practical). The effectiveness test was conducted through pre-tests and post-tests on 29 students of class VII A at SMPN 2 Jalaksana, which showed an increase in the average score from 69.8 to 90.2 with an N-gain of 0.7 (moderate category). These results indicate that the developed e-module is suitable for use as an effective interactive learning media that can enhance students' creative mathematical thinking skills.